2017
DOI: 10.4103/0366-6999.204107
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Tenofovir Disoproxil Treatment for Chronic Hepatitis B Patients with Genotypic Resistance to Other Nucleoside Analogues

Abstract: Background:Tenofovir disoproxil (TDF) is a promising salvage therapy for patients with chronic hepatitis B (CHB) who failed regimens of other nucleoside analogues (NAs). In this study, we aimed to investigate the clinical efficacy and safety of TDF monotherapy in Chinese CHB patients with genotypic resistance.Methods:A total of 33 CHB patients who had failed treatment with other NAs and had genotypic resistance were switched to TDF monotherapy for 48 weeks. Patients’ demographic data (age, sex, history of hepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
3
4
0
Order By: Relevance
“…TDF-based ART can effectively restore the immune function of PLWH as reflected by the rapid increase in CD4 + T cell count in the first 12 weeks of ART and the slow increase in CD4 + T cell count afterwards. These results also have been supported by other studies (Wu et al, 2016;Gazzard et al, 2014;Zhou et al, 2017;Amiel et al, 2014). Compared with other regimens, TDF-based regimens showed no difference in the gain of CD4 + T cell count (Hemkens et al, 2015).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…TDF-based ART can effectively restore the immune function of PLWH as reflected by the rapid increase in CD4 + T cell count in the first 12 weeks of ART and the slow increase in CD4 + T cell count afterwards. These results also have been supported by other studies (Wu et al, 2016;Gazzard et al, 2014;Zhou et al, 2017;Amiel et al, 2014). Compared with other regimens, TDF-based regimens showed no difference in the gain of CD4 + T cell count (Hemkens et al, 2015).…”
Section: Discussionsupporting
confidence: 78%
“…Many studies have demonstrated that ART can lead to a significantly increased prevalence of dyslipidemia (Wu et al, 2016;Zhou et al, 2017;Huang et al, 2015a;Molina et al, 2008;Ortiz et al, 2008), and HIV itself could result in dyslipidemia (Shen et al, 2015). The prevalence of hypercholesteremia and hypertriglyceridemia in ART-naïve HIV-infected patients were similar to previous reports from China (Shen et al, 2015) and Africa (Armstrong et al, 2011).…”
Section: Discussionsupporting
confidence: 77%
“…TDF and TDF+ETV have been previously reported to be efficient for the treatment of ETV-resistant patients [33−36], including Chinese patients [31,37,38]. Our results reinforced the fact that TDF-based rescue therapy was efficient in ETV-resistant patients who had an inadequate VR upon ADV+ETV rescue therapy.…”
Section: Discussionsupporting
confidence: 85%
“…In addition, virological response rates increased during treatment. [129][130][131][132][133][134][135][136][137][138][139] Tenofovir alafenamide fumarate tablets (TAF): In a global phase III clinical trial, 581 HBeAg-positive CHB patients (which excluded patients with decompensated cirrhosis) received TAF treatment for 48 weeks. HBV DNA levels were <29 IU/mL in 64% of patients and ALT levels returned to normal in 72% of patients.…”
Section: Entecavir (Etv)mentioning
confidence: 99%